2014
DOI: 10.4314/tjpr.v13i6.8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by Methyl Alcohol Extract of <i>Enteromorpha linza</i> (Linnaeus) J Agardh in U937 Human Leukemia Cells

Abstract: Purpose: To investigate the anti-cancer effect of methyl alcohol extract of Enteromorpha linza (Linnaeus) J. Agardh (MEEL) in U937 human leukemia cells. Methods: Cytotoxicity was evaluated by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A marked decrease in cell viability was observed under DNX, paralleling the results acquired from the MTT analysis. Interestingly, such effects can potentially be ascribed to DNX's pro-apoptotic attributes, as delineated in the previous literature [40,41,45,65]. Despite this, in a control setting, HFF-1 cell viability remained high at 91% with a 20 µM DNX concentration.…”
Section: Discussionmentioning
confidence: 70%
“…A marked decrease in cell viability was observed under DNX, paralleling the results acquired from the MTT analysis. Interestingly, such effects can potentially be ascribed to DNX's pro-apoptotic attributes, as delineated in the previous literature [40,41,45,65]. Despite this, in a control setting, HFF-1 cell viability remained high at 91% with a 20 µM DNX concentration.…”
Section: Discussionmentioning
confidence: 70%
“…Thus, the compounds that have a potential to restore apoptosis have a great potential to develop as anticancer drugs (Sanjeewa et al 2017). Choi et al (2014) attempted to evaluate the anticancer properties of methyl alcohol extract separated from E. linza on human leukemia cells (U937). In this study, the authors demonstrated the extract has a potential to induce apoptosis in U937 cell via upregulated expression of death receptors 4 and 5 and downregulated expression of antiapoptotic proteins such as Bcl-2 and Bcl-xL and IAP family proteins (50~300 μg/mL).…”
Section: Anticancer Propertiesmentioning
confidence: 99%
“…There are more than 600 different carotenoids in nature, and they are common natural pigments [19]. Although some natural carotenoids, such as astraxanthin, β-carotene, and lycopene have been used as food coloring for many years, it has recently been an area of intense study in investigating its potential to prevent epithelial cancer and chronic diseases, with the discovery of antioxidant activity [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Although some natural carotenoids, such as astraxanthin, β-carotene, and lycopene have been used as food coloring for many years, it has recently been an area of intense study in investigating its potential to prevent epithelial cancer and chronic diseases, with the discovery of antioxidant activity [20,21]. Carotenoids are found in many bacteria and are found in a wide variety of phyla, not only photosynthetic but also non-photosynthetic species [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation